Interactive thermal tissue reactions of 7‐MHz intense focused ultrasound and 1‐MHz and 6‐MHz radiofrequency on cadaveric skin. Issue 2 (15th October 2018) - Kim, Heesu; Ahn, Keun Jae; Lee, Sugun; Park, Henry; Cho, Sung Bin
Abstract: Background: Intense focused ultrasound (IFU) and radiofrequency (RF) systems generate thermal tissue reactions in multiple zones in the skin, with the microscopic features thereof varying according to energy sources and treatment parameters. Objective: To evaluate interactive thermal tissue reactions of IFU and RF in cadaveric skin. Methods: Thermal reaction patterns generated by IFU, invasive bipolar RF, and non‐invasive monopolar RF treatments were analyzed in cadaveric skin of the inner thigh. Additionally, combination treatment, including IFU and invasive bipolar RF, IFU and non‐invasive monopolar RF, invasive bipolar RF and IFU, and non‐invasive monopolar RF and IFU, was delivered to cadaveric skin and microscopically evaluated. Results: Combination treatment with 1.5‐mm IFU followed by 1.5‐mm invasive RF elicited multiple thermal injury zones of coagulation and ablation in the mid to lower dermis. Therein, IFU‐induced thermal reactions were indistinguishable from RF‐induced thermal reactions. Non‐invasive RF treatment on IFU‐pretreated cadaveric tissue specimens exhibited greater degrees of thermal injury, with wider and deeper penetration, compared to non‐invasive RF treatment alone. Furthermore, RF‐pretreated tissues showed marked differences in the patterns of IFU‐induced thermal tissue reactions. Conclusion: Our data suggest that combination treatments with IFU and RF elicit various patterns of interactive thermal tissue reactions.